Kaashaf-e-Israar (Hayat-o-Tasaneef-e-Sufi Atta Muhammad Qadri) - Nafees Iqbql, Dr. (Lahore Sang-e-Meel Publications, 2010)
Hayat-o-Tasaneef-e-Sufi Atta Muhammad Qadri.
Urdu Biography.
Keywords: Urdu Biography -- Urdu Literature